TiO2 Simultaneous Enrichment, On-Line Deglycosylation, and Sequential Analysis of Glyco- and Phosphopeptides - Chen, Cheng; Zhang, Xiaofei; Dong, Xuefang; Zhou, Han; Li, Xiuling; Liang, Xinmiao (Frontiers in Chemistry, 2021)
Reversible protein glycosylation and phosphorylation tightly modulate important cellular processes and are closely involved in pathological processes in a crosstalk dependent manner. Because of their significance and low abundances of glyco- and phosphopeptides, several strategies have been developed to simultaneously enrich and co-elute glyco- and phosphopeptides. However, phosphopeptides slowly hydrolyze during deglycosylation and the co-existence of deglycosylated peptides and phosphopeptides aggravates the mass spectrometry analysis. Herein we developed a novel strategy to analyze glyco- and phosphopeptides based on simultaneous enrichment with TiO2, on-line deglycosylation and collection of deglycosylated peptides, and subsequent elution of phosphopeptides. To optimize on-line deglycosylation conditions, the solution pH, buffer types and concentrations, and deglycosylation time were investigated. The application of this novel strategy to 100 μg mouse brain resulted in 1,405 glycopeptides and 2,022 phosphopeptides, which were 2.4 and 1.4 folds of those enriched with the reported method. This study will expand the application of TiO2 and may shed light on simultaneous monitoring of multiple protein post-translational modifications.